2004
DOI: 10.1021/bm049765f
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization and Stabilization of Recombinant Multimeric Uridine and Purine Nucleoside Phosphorylases fromBacillus subtilis

Abstract: We selected the PnpI/PupG (PNP) with specificity for ribo- and deoxyriboguanosine and ribo- and deoxyriboinosine and the Up/Pdp (UP) with specificity for uridine, thymidine, and deoxyuridine from the purine and pyrimidine salvage pathway of the Gram-positive bacterium Bacillus subtilis. Then, an extensive study of the UP (uridine phosphorylase) and PNP (purine nucleoside phosphorylase) immobilization and stabilization was carried out: optimal UP preparation was achieved by immobilization onto Sepabeads coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 31 publications
2
69
0
Order By: Relevance
“…[32,33] Initially, the experiments were performed by loading a low amount of enzyme on the carrier (0.1-0.5 mg g…”
Section: Dmdnk Immobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…[32,33] Initially, the experiments were performed by loading a low amount of enzyme on the carrier (0.1-0.5 mg g…”
Section: Dmdnk Immobilizationmentioning
confidence: 99%
“…[32] Immobilization on Sepabeads-PEI and Cross-Linking with Aldehyde Dextran Immobilization on Sepabeads-PEI and stabilization by cross-linking with 10% oxidized dextran was performed by slightly modifying the procedure previously described. [32] Briefly, the activated carrier (1.0 g) was suspended in 5 mM phosphate buffer pH 7.5 containing the soluble DmdNK (0.1-2.0 mg) in a total volume of 14 mL. The suspension was kept under mechanical stirring at room temperature and after 1 hour aldehyde dextran (1.4 mL) was added and allowed to stir for an additional hour.…”
Section: Preparation Of Sepabeads-peimentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Several procedures based on the "transglycosylation" reaction (Scheme 1) have been employed (using both isolated enzymes and whole cells) to prepare a wide variety of nucleosides. [4][5][6][7][8][9][10][11] Structural analysis revealed that there are two distinct families of NPs: NPI and NPII. Members of the NPI family show either a trimeric or a hexameric quaternary structure.…”
Section: Introductionmentioning
confidence: 99%
“…In Escherichia coli, exogenous ribonucleosides are predominantly metabolized by nucleoside phosphorylases encoded by deoD, udp and xapA, while NHs encoded by rihA, rihB and rihC have been reported and play a minor role (Koszalka et al, 1988;Petersen & Moller, 2001). In the case of the genus Bacillus, the metabolic pathways mediated by only nucleoside phosphorylases have been reported and characterized (Hamamoto et al, 1996;Rocchietti et al, 2004), whereas in the yeast Saccharomyces cerevisiae, purine ribonucleosides, inosine and guanosine, and pyrimidine ribonucleosides, cytidine and uridine, were salvaged by purine nucleoside phosphorylase (encoded by pnp1) and uridine ribohydrolase (encoded by urh1), respectively (Desgranges et al, 2001;Kurtz et al, 2002;Mitterbauer et al, 2002). In addition, NHs, but not nucleoside phosphorylases, are crucial enzymes in purinepyrimidine salvage in protozoan parasites (Parkin et al, 1991): an inosine-uridine NH and a guanosine-inosine NH from Crithidia fasciculata (Estupinan & Schramm, 1994;Degano et al, 1996), a purine-specific inosine-adenosineguanosine NH from Trypanosoma brucei subsp.…”
Section: Introductionmentioning
confidence: 99%